ANALISIS KESESUAIAN KONTEN IPS DENGAN KOMPETENSI DASAR PADA BUKU SISWA KELAS IV SD : Penelitian Kualitatif Analisis Isi pada Uraian Materi dalam Buku Siswa Kelas IV SD/MI Terbitan Kementerian Pendidikan dan Kebudayaan - Hanina Aulia Zakka, - (2020)
Penelitian ini bertujuan untuk memverifikasi kesesuaian konten IPS pada buku siswa kelas IV SD/MI dengan Kompetensi Dasar dimensi pengetahuan dan keterampilan. Verifikasi difokuskan pada uraian materi. Pendekatan penelitian menerapkan pendekatan kualitatif dengan metode analisis konten. Sumber data penelitian adalah buku siswa kelas IV SD/MI terbitan Kementerian Pendidikan dan Kebudayaan Edisi Revisi 2017. Teknik pengumpulan data menggunakan studi dokumentasi. Teknik analisis data menerapkan analisis konten buku siswa tema 1 sampai dengan tema 9. Hasil penelitian ditemukan bahwa pada buku siswa kelas IV SD sebagai berikut: (1) terdapat kesesuaian antara konten IPS dengan Kompetensi Dasar dimensi pengetahuan faktual dan pengetahuan konseptual pada tema pembelajaran kecuali tema 5, dimensi pengetahuan prosedural hanya terdapat pada tema 3 dan 4, tidak ditemukan dimensi pengetahuan metakognitif pada semua tema, (2) terdapat kesesuaian konten IPS dengan Kompetensi Dasar dimensi keterampilan berpikir nalar pada tema 2, 5, 7, dan dimensi keterampilan bertindak pada tema 3 dan 7. ----- This research aimed to verification the suitability of social studies content with basic competencies on the dimensions of knowledge and skills in the books of grade fourth elementary school. The focus of this verification is the description of the material. The research used qualitative approach with content analysis method. The data source of this research was taken by the books of grade fourth elementary schools that published by the Ministry of Education and Culture, Edition 2017. The data collection techniques used were documentary study. The data analysis technique used analysis content of students' book on themes 1 until 9. The research outcomes were found that in the fourth grade elementary school students' books as follows: (1) there were compatibility between social studies content and basic competencies in the dimensions of factual and conceptual knowledge in student books, except in theme five, the dimensions of procedural knowledge only in theme three and four student books. Metacognitive knowledge is not found in all themes of students' book, (2) there were compatibility between social studies content and basic competencies in the dimensions reasonable thinking skills only in student books on themes two, five, and seven. There were compatibility between social studies content and basic competencies in the dimensions of acting skills only in student books on themes three and seven.